Environmental Influences on Human Subsistence Strategies in Southwest China During the Bronze Age: A Case Study at the Jiangxifen Site in Yunnan - Lu, Minxia; Li, Xiaorui; Wei, Wenyu; Lu, Yiwen; Ren, Lele; Ma, Minmin (Frontiers in Earth Science, 2021)
The study of human dietary structures is an effective means of elucidating the subsistence patterns of our prehistoric ancestors and can highlight the processes through which humans interacted with the environment. We conducted stable isotope and archeobotanical analyses of human, animal, and plant remains at the Jiangxifen site, dated to ~900–400 BC, to explore human paleodiets and determine the environmental adaptation strategies adopted by humans in the middle valley of the Jinshajiang River in Yunnan Province. Humans predominantly consumed C4 foods (e.g., millet) and C4 food-fed animal protein sources, with smaller contributions from C3 food plants (e.g., rice) and C3 food-fed animal protein sources. We argue that the local dry-hot environment was the reason for the accessibility of C4 plants in the studied area. A comparison of our results with previously published archeobotanical data and isotopic evidence from human bones in other Bronze Age sites in Yunnan Province revealed high spatial variability in human’s diets and subsistence strategies during this period. These differences were caused by the highly varying living environment of each region, which was related to fragmentation resulting from the geomorphological features of Yunnan Province.